PENGARUH KARTU PINTAR IBU TERHADAP PENGETAHUAN IBU DALAM PENATALAKSANAAN DIARE PADA ANAK DI PRE HOSPITAL PADA MASA PANDEMI COVID-19 DI LUBUKLINGGAU - Wijaya, Sapondra; Soewito, Bambang; Umi, Mawadda; Fitria, Devi; Saputri, Vina Ayu (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p05, 2021)
Abstract Restrictions on activities outside the home were imposed during the Covid-19 pandemic to minimize the spread of the Covid-19 virus. One of the activities outside the home that is often carried out is taking medication at a health facility. Children are an age group that is vulnerable to disease exposure. Many diseases that often occur in children, including diarrhea. One of the places prone to disease transmission is in health facilities, while children with diarrhea tend to be taken by their parents to health facilities. Therefore, there is a need for socialization about the handling of diarrhea in the pre-hospital phase or at home, so that children can be treated at home first if the conditions allow. The purpose of this study was to determine the effect of the Mother's Smart Card, which is a simplification of the MTBS book, on knowledge in managing diarrhea in children in the pre-hospital phase. This study used a quasi-experimental design with a pre and post test approach with purposive sampling technique on 30 mothers. Maternal knowledge is measured from knowledge of diarrhea and its management. The results of data analysis using the paired t-test showed that there was a significant effect of the Mother's Smart Card on the mother's knowledge in managing children's diarrhea at home with a value of p = 0.000. This means that the Mother's Smart Card can increase maternal knowledge in the management of pre-hospital phase children's diarrhea. This result is expected that the Mother's Smart Card can be a reference in increasing maternal knowledge, and minimizing treatment in inappropriate health facilities that can be at risk of Covid-19 transmission. Keywords: Children, Covid-19, Diarrhea, Mommy Smart Card, Pre Hospital